Whole-Body Prolyl Hydroxylase Domain (PHD) 3 Deficiency Increased Plasma Lipids and Hematocrit Without Impacting Plaque Size in Low-Density Lipoprotein Receptor Knockout Mice - Demandt, Jasper A. F.; van Kuijk, Kim; Theelen, Thomas L.; Marsch, Elke; Heffron, Sean P.; Fisher, Edward A.; Carmeliet, Peter; Biessen, Erik A. L.; Sluimer, Judith C. (Frontiers in Cell and Developmental Biology, 2021)
Background and aims: Atherosclerosis is an important cause of clinical cardiovascular events. Atherosclerotic plaques are hypoxic, and reoxygenation improves plaque phenotype. Central players in hypoxia are hypoxia inducible factors (HIF) and their regulators, HIF-prolyl hydroxylase (PHD) isoforms 1, 2, and 3. PHD inhibitors, targeting all three isoforms, are used to alleviate anemia in chronic kidney disease. Likewise, whole-body PHD1 and PHD2ko ameliorate hypercholesterolemia and atherogenesis. As the effect of whole-body PHD3 is unknown, we investigated the effects of germline whole-body PHD3ko on atherosclerosis. Approach and Results: To initiate hypercholesterolemia and atherosclerosis low-density lipoprotein receptor knockout (LDLrko) and PHD3/LDLr double knockout (PHD3dko), mice were fed a high-cholesterol diet. Atherosclerosis and hypoxia marker pimonidazole were analyzed in aortic roots and brachiocephalic arteries. In contrast to earlier reports on PHD1- and PHD2-deficient mice, a small elevation in the body weight and an increase in the plasma cholesterol and triglyceride levels were observed after 10 weeks of diet. Dyslipidemia might be explained by an increase in hepatic mRNA expression of Cyp7a1 and fatty acid synthase, while lipid efflux of PHD3dko macrophages was comparable to controls. Despite dyslipidemia, plaque size, hypoxia, and phenotype were not altered in the aortic root or in the brachiocephalic artery of PHD3dko mice. Additionally, PHD3dko mice showed enhanced blood hematocrit levels, but no changes in circulating, splenic or lymphoid immune cell subsets. Conclusion: Here, we report that whole-body PHD3dko instigated an unfavorable lipid profile and increased hematocrit, in contrast to other PHD isoforms, yet without altering atherosclerotic plaque development.